2009
DOI: 10.1111/j.1754-9485.2009.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of T2 hyperintense spinal cord lesions: Part B

Abstract: Hyperintense spinal cord signal on T2-weighted images is seen in a wide-ranging variety of spinal cord processes. Causes including simple MR artefacts, trauma, primary and secondary tumours, radiation myelitis and diastematomyelia were discussed in Part A. The topics discussed in Part B of this two part series include multiple sclerosis, subacute combined degeneration of the spinal cord, cord infarction, arteriovenous shunts, transverse myelitis, neurosarcoidosis, AIDS-associated vacuolar myelopathy, and syrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…MRI imaging is definitely sensitive for the diagnosis of a SCIWORA injury. 36 However, owing to the nature of the SCIWORA injury, it could be damaging the blood supply of the nerve. One hundred and twenty (28%) of the initial MRIs were normal; this is probably because the blood supply had been slowly 37 showed that adults most commonly presented with AIS grade C (39.7%) and grade D ( 22.8%).…”
Section: Discussionmentioning
confidence: 99%
“…MRI imaging is definitely sensitive for the diagnosis of a SCIWORA injury. 36 However, owing to the nature of the SCIWORA injury, it could be damaging the blood supply of the nerve. One hundred and twenty (28%) of the initial MRIs were normal; this is probably because the blood supply had been slowly 37 showed that adults most commonly presented with AIS grade C (39.7%) and grade D ( 22.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Very few disease entities will have this classic MR appearance in isolation; acquired immune deficiency syndrome-associated vacuolar myelopathy and copper deficiency are some of the few entities known to be radiologically identical to SCD. (11,12) Demyelination, infection, autoimmune processes, neoplasm and vascular entities can also mimic SCD on MR imaging, yet these processes can potentially be differentiated on close inspection. (11) A recent review of T2 hyperintense spinal cord lesions by Bou-Haidar et al provides a concise outline for their differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] The differential diagnosis for progressive spastic paraplegia includes degenerative, demyelinating, infectious, inflammatory, neoplastic, nutritional and vascular disorders. [9,10] Normal abdominal USG, cranial and spinal MRI's and history of chronic alcoholism provided the diagnosis of SCD due to chronic alcohol intake.…”
Section: Discussionmentioning
confidence: 99%